2001
DOI: 10.1128/jvi.75.2.850-856.2001
|View full text |Cite
|
Sign up to set email alerts
|

Both Carboxy- and Amino-Terminal Domains of the Vaccinia Virus Interferon Resistance Gene, E3L, Are Required for Pathogenesis in a Mouse Model

Abstract: The vaccinia virus (VV) E3L gene is responsible for providing interferon (IFN) resistance and a broad host range to VV in cell culture. The E3L gene product contains two distinct domains. A conserved carboxy-terminal domain, which is required for the IFN resistance and broad host range of the virus, has been shown to bind double-stranded RNA (dsRNA) and inhibit the antiviral dsRNA-dependent protein kinase, PKR. The aminoterminal domain, while conserved among orthopoxviruses, is dispensable in cell culture. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
201
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(210 citation statements)
references
References 48 publications
7
201
1
1
Order By: Relevance
“…Our findings suggest that these HCMV genes sequester PKR away from its activator, cytoplasmic dsRNA generated during the course of viral infection, and also from its target substrate, cytoplasmic ribosome-associated eIF2␣ that is participating in translation initiation. Since PKR plays a significant role in the life cycle of numerous viruses (9,12,20,29,48), further studies of how these HCMV genes modulate PKR activity are likely to contribute to our understanding of HCMV disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that these HCMV genes sequester PKR away from its activator, cytoplasmic dsRNA generated during the course of viral infection, and also from its target substrate, cytoplasmic ribosome-associated eIF2␣ that is participating in translation initiation. Since PKR plays a significant role in the life cycle of numerous viruses (9,12,20,29,48), further studies of how these HCMV genes modulate PKR activity are likely to contribute to our understanding of HCMV disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These animals were intranasally infected with 10 6 p.f.u. VACV-WR or GP2V in 10 ml PBS (Brandt & Jacobs, 2001). Mice from the negative control group were inoculated intranasally with 10 ml PBS.…”
mentioning
confidence: 99%
“…The IFN resistance gene (ORF 020) is an orthologue of VACV E3L, which is essential for the broad host-range of VACV in vitro and affects virulence in vivo (Brandt & Jacobs, 2001;Vijaysri et al, 2003Vijaysri et al, , 2008. As a result of the variation seen between the N-terminal domains of the ORFV and BPSV proteins, Delhon et al (2004) suggested that this domain might have a role to play in host range and pathogenesis.…”
Section: Hautaniemi and Othersmentioning
confidence: 99%